Maintenance of Francisella tularensis 15 RIEH and Brucella abortus 19 BA Strains in a Viable State by Means of Deep Freezing - A. N. Malakhaeva; O. Yu. Lyashova; O. P. Plotnikov; A. V. Osin (Проблемы особо опасных инфекций, 2015)
Assessed are the methods for storage of microorganisms in a viable state under various technological conditions for a period of two years. Compared is the survivability of the test-strains of tularemia and brucellosis agents (exemplified by Francisella tularensis 15 RIEH and Brucella abortus 19 BA) when stored on the nutrient media at temperatures raging 0 °C up +8 °C and at -70 °C for over a year. Made has been an estimate of survivability of the vaccine strains stored at -70 °C within two years term. It is determined that optimum media for storing the stated above microorganisms with no changes in their morphological characteristics at -70 °C are sucrose-gelatin agar and Albimi broth with 10 % glycerin. Demonstrated is the fact that it is more efficient to conserve microorganisms stored in working collections by way of deep freezing.